Past Biodiversity: Japanese Historical Monographs Document the Epibiotic Barnacles and Cold-Stunning Event of the Hawksbill Turtle Eretmochelys imbricata - Hayashi, Ryota (Frontiers in Ecology and Evolution, 2021)
he historical monographs called ‘Honzou Gaku’ present the first record of cold-stunning of a hawksbill turtle Eretmochelys imbricata (Linnaeus, 1766) in the Echigo region of Japan during the Edo period (1600–1868), and the barnacles attached to the turtle were identified as Platylepas hexastylos (Fabricius, 1798). Analysis of this finding adds substantial knowledge to our understanding of the life history of the hawksbill turtles along the coast of Japan. As reported in this study, literature on the historical heritage of other animals or plants can also provide information about their past biodiversity.